Usefulness of the insulin tolerance test in patients with type 2 diabetes receiving insulin therapy. Issue 3 (30th September 2013) - Okita, Kohei; Iwahashi, Hiromi; Kozawa, Junji; Okauchi, Yukiyoshi; Funahashi, Tohru; Imagawa, Akihisa; Shimomura, Iichiro
Abstract Aims/Introduction To establish the validity of the plasma glucose disappearance rate (KITT), derived from an insulin‐tolerance test (ITT), for evaluating the insulin sensitivity of patients with type 2 diabetes after insulin therapy. Materials and Methods In the first arm of the study, 19 patients with poorly controlled diabetes were treated with insulin and underwent an ITT and a euglycemic clamp test (clamp‐IR). The relationship between the insulin resistance index, as assessed by both the clamp‐IR and KITT tests, was examined. In the second arm of the study, the relationships between KITT values and various clinical parameters were investigated in 135 patients with poorly controlled diabetes, after achieving glycemic control with insulin. Results In study 1, a close correlation between KITT and the average glucose infusion rate during the last 30 min of the standard clamp‐IR test (M‐value) was noted (P < 0.001). In study 2, body mass index (P = 0.0011), waist circumference (P = 0.0004), visceral fat area (P = 0.0011) and the log‐transformed homeostasis model assessment of insulin resistance value (P = 0.0003) were negatively correlated with the log‐transformed KITT. High‐density lipoprotein cholesterol (P = 0.0183), low‐density lipoprotein cholesterol (P = 0.0121) and adiponectin (P = 0.0384) levels were positively correlated with the log‐transformed KITT. Conclusions The ITT is a valid and useful test for evaluating the insulin sensitivity of patients with diabetes, even after treatment with insulin.